Teachers' Readings: Books, Libraries, and School - Galvao Ribeiro Ferreira, Eliane Aparecida [UNESP]; Valente, Thiago Alves (Univ Federal Espirito Santo, 2015)
This article presents results about the investigation working A leitura e os jovens leitores: praticas de letramento no Norte Pioneiro-PR, developed at the Universidade Estadual do Norte do Parana (UENP), with financial support by Fundacao Araucaria and executed in the Universidade Estadual do Parana, Campus Cornelio Procopio, for researchers of Centro de Letras, Comunicacao e Artes (CLCA), with researchers partners of groups like the Literatura e Leitura na Escola. (Unesp-FCL/Assis). This aim was done between april 2012 and november 2014 had as subject of research the programs/projects to books and reading among teens of the High School at Basic Education of Parana State on Brazil. As estrategy were applied questions for the 33 teachers of public schools on Parana about literature reading while they studied PDE's modules integrated in the Programa de Desenvolvimento Educacional (PDE).
Keywords: Reading; Reader; Public Policy